Growth and development of the cupuaçu fruit (theobroma grandiflorum [willd. ex spreng.] schum.) in the western colombian amazon (2012)
Studies of growth and optimal harvest time of cupuaçu are vital to ensure fruit quality and reduce post-harvest losses. This studied looked at growth and fruit development of cupuaçu from fruit set to ripening. The measurements analyzed included diameter (longitudinal and equatorial), fresh and dry weight, color, pH, titratable acidity (TA), total soluble solids (TSS) and respiratory rate (RR). Three sigmoid states were observed during fruit growth: cell division (S1), maximum growth (S2), which corresponds to cell expansion and growth stabilization and maturation (S3). The time between fruit set and physiological maturity was 117 days. The cupuaçu fruit reached physiological maturity when it showed changes in pulp color (H* = 97.1±1.8°), which coincided with a TSS of about 5.7±0.8°Brix, which were a good index of maturity along with days after fruit set. The respiration pattern of the cupuaçu fruit was climacteric, with a peak of 156.24±42.5 mg CO2 kg-1 h-1 124 days after fruit set. No ethylene was detected before harvest, but was detected in some fruits postharvest.